Mapping structure, process and outcomes in the removal of low-value care practices in Canadian intensive care units: protocol for a mixed-methods exploratory study - Henry Thomas Stelfox; Daniel Niven; Jeanna Parsons Leigh; Jennie Petersen; Chloe de Grood; Liam Whalen-Browne (BMJ Open)
Introduction The challenge of implementing best evidence into clinical practice is a major problem in modern healthcare that can result in ineffective, inefficient and unsafe care. There is a growing body of literature which suggests that the removal or reduction of low-value care practices (ie, deadoption) is integral to the delivery of high-quality care and the sustainability of our healthcare system. However, currently very little is known about deadoption practices in Canada. We propose to map the current state of deadoption in Canadian intensive care units (ICUs). A key deliverable of this work will include development of an inventory of barriers, facilitators and potential implementation strategies for guiding the deadoption efforts.Methods and analysis We will use Canadian adult general systems ICUs as our laboratory of investigation and employ a two-phased sequential exploratory mixed-methods approach: (1) semi-structured interviews with critical care stakeholders to develop an understanding of the structure (ie, healthcare context), process (ie, actions and events in healthcare) and outcomes (ie, effects on health status, quality, knowledge or behaviour) of deadoption (phase I) and (2) surveys with a broader sample of critical care stakeholders to further identify important barriers and facilitators, as well as potential implementation strategies (phase II). Interview data will be analysed through qualitative content analysis and survey data will be analysed through quantitative analyses to identify top barriers and facilitators, as well as top rated strategies.Ethics and dissemination Ethical approval has been obtained through the University of Calgary Research Ethics Board (REB 17–2153). Participants involved will have the opportunity to provide feedback on the final written reports to support accurate representation of the data. The findings of this study will be disseminated through peer-reviewed publications and oral presentations with critical care stakeholders across Canada. Patient and family partners will receive an executive summary of the findings.